2018
DOI: 10.1007/s40618-017-0815-7
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effects of the l-dopa and insulin tolerance tests on cortisol secretion

Abstract: The results of the current study confirm that the L-dopa test is a reliable test of cortisol secretion. As such, this test may be applicable to assessments of the hypothalamic-pituitary-adrenal axis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…In addition, nausea/vomiting was observed in 53 (62.4%) of the patients during the L-dopa test, and peak cortisol responses were similar in patients with and without side effects. This finding was similar to the results of our previous study and the two studies of Marakaki et al [5][6][7] Taken together, these findings suggest that the hypothesis that an increase in cortisol and ACTH secretion occurs as a result of side effects such as nausea/vomiting during the L-dopa test is not valid.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…In addition, nausea/vomiting was observed in 53 (62.4%) of the patients during the L-dopa test, and peak cortisol responses were similar in patients with and without side effects. This finding was similar to the results of our previous study and the two studies of Marakaki et al [5][6][7] Taken together, these findings suggest that the hypothesis that an increase in cortisol and ACTH secretion occurs as a result of side effects such as nausea/vomiting during the L-dopa test is not valid.…”
Section: Discussionsupporting
confidence: 91%
“…18 The results of the experimental studies support that the dopamine agonist stimulates the HPA axis through various pathways and therefore increases the secretion of cortisol from the adrenal gland. In our previous study 7 and in the study by Marakaki et al 5 , ACTH levels were also shown to increase in correlation with serum cortisol responses during the L-dopa test, suggesting that the possible physiological mechanism of the cortisol-secreting effect of L-dopa is the increase in ACTH.…”
Section: Discussionmentioning
confidence: 55%
See 3 more Smart Citations